A Vulnerability Risk Index of Self‐Neglect in a Community‐Dwelling Older Population. Issue 4 (11th December 2019) - Wang, Bei; Hoover, Donald R.; Beck, Todd; Dong, XinQi
Abstract : BACKGROUND: The only way to systematically screen for self‐neglect among older adults is through in‐home observations, which are often difficult and unfeasible for healthcare providers. To fill this gap, we need a robust and efficient prognostication tool to better treat and prevent self‐neglect among older adults. OBJECTIVES: To develop a predictive index that can be used to assess risk prognostication of the onset of self‐neglect among community‐dwelling older populations. DESIGN: Two waves of longitudinal data from the Chicago Health and Aging Project (CHAP), collected during 2008 to 2012 with approximately 3‐year follow‐up intervals. SETTING: Non‐Hispanic black or non‐Hispanic white community‐dwelling older adults in three adjacent neighborhoods in Chicago, IL. PARTICIPANTS: A total of 2885 individuals who were participants of the CHAP study. MEASUREMENTS: The main outcomes are incident self‐neglect cases. A total of 86 potential predictors were considered in the domains of sociodemographic and socioeconomic, general well‐being, health behavior, medical health, medicine/healthcare, cognitive function, physical well‐being, social well‐being, and psychological well‐being. RESULTS: The 3‐year self‐neglect incidence rate is 241 (8.4%). A 10‐item predictive model (with a c‐statistic of 0.76) was developed using stepwise selection in multivariable logistical regression models. After corrections of overfitting by validating in 100 bootstrapping samples, the predictive accuracy of the model dropped to 0.71, suggesting at least moderate overfitting. A point‐based risk index was developed based on parameter estimates of each predictive factor in the final logistic model. The index has an area under the receiver operating characteristic curve of 0.76. CONCLUSION: The study developed an efficient index with good predictive ability of self‐neglect. Further external validation and impact studies are necessary before practitioners can apply this index to determine risk of self‐neglect among other community aging populations. J Am Geriatr Soc 68:809–816, 2020